EXPERT EVALUATION OF THE ERGATIC SYSTEMS OPERATORS ACTIVITY - Stenin, A. A.; Gubskiy, A. N.; Polshakova, O. M. (Radio Electronics, Computer Science, Control, 2013)
At present time, search for ways of improving ergatic systems is going on several fronts. The article highlights the direction related to the reevaluation of the role of the human factor. The urgent need for the development of this trend is due to the fact that for modern ergatic systems the function and role of human operator in them have changed. In the experimental study of the operators, in most cases, the method of experimental evaluations works. The formation of a coherent group of experts is one of the crucial factors to obtain reliable data. In this paper order to form such a group of experts an algorithm of focused view and filtration of the expert group was proposed. Furthermore, the article defines the stages of the peer review for ergatic system operators and tasks at each of these stages.